A coking and creep resistant cracking furnace tube and its preparation method
By using Fe-Ni-Cr alloy material on the ethylene cracking furnace tube, a dense composite metal oxide layer is formed, which solves the problem that the furnace tube is prone to coking in high temperature environments, and improves the anti-coking and creep resistance, extends the use cycle and improves the ethylene production.
Patent Information
- Application Number
- CN202211619847.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The existing ethylene cracking furnace tubes are prone to coking in high temperature environments, resulting in a decrease in material elongation and severe embrittlement, which affects service life.
Using Fe-Ni-Cr alloy material, a dense composite metal oxide layer is formed on the surface, the outer layer is a MnCr2O4 spinel oxide layer, and the inner layer gradually changes into (Al, Cr)2O3 corundum oxide layer and Al2O3 oxide layer. The oxide film is formed by a two-step heating method.
The anti-coking and creep resistance of the furnace tube is achieved, the service cycle is extended, the coking frequency is reduced, the ethylene production is improved, and the implementation of process parameters is simplified.
Smart Images

Figure CN115948171B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cracking furnace tubes, and mainly relates to a cracking furnace tube with anti-coking and anti-creep properties and a preparation method thereof. Background Art
[0002] In the process of hydrocarbon cracking, in addition to the production of various small molecule hydrocarbon products, a small amount of coke ash is also produced. These cokes are mainly composed of hundreds of carbon atoms condensed together (the carbon content is more than 95%) and contain a small amount of hydrogen. This type of carbon is called coke, which is an inevitable by-product in the thermal cracking process of hydrocarbon raw materials. During the cracking process of hydrocarbons, the coke deposition process on the inner wall of the tubular cracking furnace is called coking. Although great progress has been made in the current ethylene production technology, the coking problem has not been completely solved.
[0003] The inner surface state of the furnace tube is one of the main factors affecting the coking characteristics of the ethylene cracking furnace tube. Fe-Ni-Cr alloy steel is a commonly used material for ethylene cracking furnace tubes. It has the characteristics of strong oxidation resistance, good resistance to sulfide corrosion, and excellent heat resistance. However, during the cracking process of the furnace tube, its inner wall is in contact with the carbon source gas and the carrier gas, so the furnace tube is inevitably coked. The metal elements such as Fe and Ni in the Fe-Ni-Cr alloy steel have strong catalytic activity in the coking carburizing atmosphere, which will catalyze coking, further leading to a decrease in the elongation of the material and severe embrittlement, which greatly affects the service life of the furnace tube.
[0004] Most of the Fe-Ni-Cr alloys currently used form a Cr2O3 oxide layer through surface pretreatment. The Cr2O3 oxide layer has good anti-coking performance at low temperatures. However, when the temperature is higher than 850°C, Cr2O3 will transform into a loose and porous form and vaporize, seriously affecting its anti-coking performance. The conversion rate of MnCr2O4 spinel carbide is lower than that of Cr2O3, and it is more stable than Cr2O3 in a coking carburizing environment, so it has excellent anti-coking performance. Summary of the invention
[0005] The purpose of the present invention is to provide an anti-coking and anti-creep alloy and a preparation method thereof. The cracking furnace tube has anti-coking and excellent anti-creep properties when cracking petroleum hydrocarbons to produce olefins. The oxide film of the existing anti-coking alloy furnace tube is mainly composed of MnCr2O4 spinel and Cr2O3 metal oxide layer. Under the high temperature environment of petroleum hydrocarbon cracking, the MnCr2O4 spinel oxide layer is easy to peel off due to thermal cycle impact, and the Cr2O3 metal oxide layer will also be vaporized, resulting in a shortened service life. The Fe-Ni-Cr alloy cracking furnace tube with excellent creep resistance provided by the present invention can form a dense and self-healing composite metal oxide layer on its surface: its outer surface layer is a MnCr2O4 spinel oxide layer, and the inner surface gradually changes to an (Al, Cr)2O3 corundum oxide layer and an Al2O3 oxide layer. The composite metal oxide layer can realize double-layer protection against coking of furnace tubes. The surface MnCr2O4 spinel and the bottom Al2O3 oxide layer can greatly improve the anti-coking performance of furnace tubes. The bottom Al2O3 metal oxide layer has strong adhesion to the furnace tube matrix and good thermal stability. It can resist multiple thermal cycle shocks, making up for the shortcoming that the surface spinel is easy to peel off, and greatly extending the service life of the furnace tube. Compared with the existing alloy furnace tube metal oxide film, the composite metal oxide film has a simpler preparation process and the required process parameters are easy to achieve. A two-step heating method is adopted: first, low-temperature low-oxygen pressure heat treatment is carried out, and then the temperature is raised for low-oxygen pressure heat treatment. Low-temperature treatment makes it easy for metal elements and oxygen to enrich to form a dense outer oxide layer, and then high-temperature treatment makes it easy for the surface MnCr2O4 spinel grains to coarsen, and the Al2O3 oxide film is transformed into α-Al2O3 to increase the stability of the oxide film.
[0006] The present invention specifically adopts the following technical scheme: a coking and creep resistant cracking furnace tube, the surface of the furnace tube has a metal oxide film with strong adhesion, self-healing ability, continuous and dense, specifically, the surface layer of the furnace tube is a MnCr2O4 spinel oxide layer, and the inner surface gradually changes to a (Al, Cr)2O3 corundum oxide layer and an Al2O3 oxide layer;
[0007] The chemical composition of the furnace tube includes, by mass percentage, 28-45% Ni, 23-35% Cr, 0-6% Al, 0-2.5% Si, 0-3% Mn and 0.005-0.4% Y;
[0008] Ni is an essential element to ensure the cyclic oxidation resistance and stability of the metal structure;
[0009] Cr can enhance the high temperature strength and cyclic oxidation ability of metals and promote the Al element;
[0010] Al can improve the alloy's anti-coking ability. In the present invention, Al forms an Al2O3 barrier layer on the alloy surface, which promotes the oxidation density with Cr. Al can decompose hydrocarbons in the direction of generating C and H, and Al2O3 is stable and strong, not easy to peel off, and has strong anti-coking performance.
[0011] As an alloy deoxidizer, Si can improve the fluidity of Al and promote Al2O3;
[0012] Mn has a high oxidation diffusion rate and can form a spinel oxidation barrier layer with the surface Cr, thus improving the alloy's anti-coking property;
[0013] Y enhances the adhesion of the oxide film and has a reinforcing effect on Al.
[0014] Furthermore, the chemical composition of the furnace tube is as follows by mass percentage: 28-45% Ni, 23-35% Cr, 0-6% Al (preferably 2-4), 0-2.5% Si, 0-3% Mn, 0.005-0.4% Y, 0-1.8% Nb, 0.5-10% W, 0.0.1-0.6% Zr, 0.05-0.7% C, and the rest is Fe;
[0015] Nb easily forms carbides and improves creep rupture strength;
[0016] W enhances the creep rupture strength of the alloy and easily forms solid solution strengthening and strengthens the austenite phase;
[0017] Zr is easy to form carbides and does not hinder the formation of Al2O3 oxide layer; rare earth metal elements are added to the alloy. Rare earth components have a great influence on the stability of oxides. They will significantly change the type and structure of oxides of the material, and a small amount of rare earth elements will have a significant impact on the thermodynamic and kinetic process of oxidation and the performance of oxide film. The addition of Y and Zr rare earths to the furnace tube promotes the formation of Al2O3 oxide layer, enhances the adhesion of the oxide film, and improves the creep performance of the furnace tube;
[0018] C can improve castability and increase high temperature creep rupture strength.
[0019] The present invention also provides a method for preparing the above-mentioned anti-coking and anti-creep cracking furnace tube, wherein the furnace tube is manufactured by centrifugal casting according to the chemical composition of the furnace tube, and then the furnace tube is heat treated in a low oxygen partial pressure water oxidation atmosphere, wherein the low oxygen partial pressure water oxidation atmosphere is a gas mixture of H2, Ar2 and H2O;
[0020] The H2 content accounts for 4% of the volume percentage of the low oxygen partial pressure water oxidation gas, the H2O content accounts for 0.001% to 3% of the volume percentage of the low oxygen partial pressure water oxidation gas, and the rest is Ar2. H2O is controlled by a micro pump, and a predetermined amount of water is set, and it is vaporized in a preheating furnace. The H2 and Ar2 mixed gas is passed into the preheating furnace at a rate of 30ml / h to mix with water vapor, and then enters the reaction furnace for oxidation reaction. The dew point is ensured by controlling the water vapor content, the required oxygen pressure is controlled, and the uncontrollable oxygen pressure is visualized to ensure the accuracy of the oxygen pressure and the accuracy of the test.
[0021] Furthermore, the heat treatment in a low oxygen partial pressure water oxidizing atmosphere is firstly a low temperature heat treatment and then a high temperature heat treatment to form a continuous and dense metal oxide film;
[0022] Low temperature heat treatment is a process to form a dense metal oxide layer in a low oxygen partial pressure water oxidation atmosphere. During low temperature heat treatment, the heat treatment temperature is 600-750℃, the heat treatment time is 5-10 hours, and the dew point of the low oxygen partial pressure water oxidation atmosphere is -10℃~-20℃. Through low temperature heat treatment, Mn, Al, and Cr diffuse from the matrix to the surface of the furnace tube for external oxidation to form a dense oxide film. The Al2O3 oxide film formed by low temperature heat treatment has a metastable structure, which is porous and lacks strength. The surface spinel grains are refined and easy to peel off.
[0023] High temperature heat treatment forms a stable and highly adhesive metal oxide layer in a low oxygen partial pressure water oxidation atmosphere. During high temperature heat treatment, the heat treatment temperature is above 1050°C, the heat treatment time is 3-10 hours, and the dew point of the low oxygen partial pressure water oxidation atmosphere is -15°C to -20°C. Through high temperature heat treatment, the Al2O3 oxide film is transformed into α-Al2O3. This corundum has a stable structure and high strength, and the surface spinel structure is coarse and not easy to peel off, thereby solving the problem of poor creep performance after adding oxidizing elements and poor adhesion of the oxide film and easy peeling in the prior art.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0025] 1) The surface of the furnace tube has a continuous and dense metal oxide film with strong adhesion and self-healing ability, which reduces the deposition of coke on the inner wall of the furnace tube, greatly prolongs the service life of the furnace tube, reduces the coke cleaning cycle of the furnace tube, and increases the ethylene production.
[0026] 2) Compared with directly forming Al2O3 metal oxide film on the surface, by forming a composite metal oxide film, the anti-coking effect of the metal oxide film is guaranteed, the process requirements for forming a metal oxide film on the alloy surface are reduced, and the composite oxide film is produced by using a low oxygen pressure similar to that used in ethylene production, which reduces costs and facilitates industrial production.
[0027] 3) Solve the disadvantage of the prior art that the creep performance deteriorates after adding oxidizing elements. By adding Zr and Y rare earth elements that are beneficial to the generation of metal oxide layers, the thickness of the metal oxide layer is increased, and the creep resistance of the furnace tube is increased;
[0028] 4) The two-step temperature-raising heat treatment in the preparation method of the present invention enhances the compactness and thermal stability of the oxide layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a SEM image of the furnace tube after heat treatment in a low oxygen partial pressure water oxidizing atmosphere in Example 1;
[0030] Figure 2 This is a SEM image of the furnace tube after air oxidation in Comparative Example 1;
[0031] Figure 3 This is the SEM picture of the commonly used furnace tube HK40 in Example 2 after being treated in a low oxygen partial pressure water oxidation atmosphere.
[0032] Figure 4 is a SEM image of the furnace tube after heat treatment of 0% Al in a low oxygen partial pressure water oxidizing atmosphere in Example 2;
[0033] Figure 5 This is a SEM image of the furnace tube after heat treatment of 6% Al in a low oxygen partial pressure water oxidizing atmosphere in Example 2. DETAILED DESCRIPTION
[0034] The embodiments take the optimal formula and process as an example to further elaborate the content of the invention.
[0035] Example 1
[0036] The preferred components are 35% Ni, 25% Cr, 4% Al, 1.5% Mn, 1.5% Nb, 1.5% Si, 1% W, 0.5% Zr, 0.4% C, 0.06% Y, and the balance is Fe in weight percentage, and are centrifugally cast into the required furnace tube. After processing, the surface is bright and free of oxide scale.
[0037] The furnace tube alloy was used to carry out low oxygen partial pressure treatment in a water oxidation test, using a gas mixture of H2, Ar2 and H2O as a low oxygen partial pressure water oxidation atmosphere. In the low oxygen partial pressure water oxidation atmosphere of the gas mixture of H2, Ar2 and H2O, the volume percentage of H2O in the low oxygen partial pressure water oxidation atmosphere gas was 0.132%.
[0038] The specific processing conditions are as follows:
[0039] Divided into low temperature treatment and high temperature treatment
[0040] Low temperature oxidation temperature: 750℃
[0041] Oxidation time 5 hours
[0042] H2 and Ar2 mixed gas flow rate: 30ml / h
[0043] Water content dew point: -15℃
[0044] High temperature treatment
[0045] High temperature treatment oxidation temperature: 1050℃
[0046] Oxidation time 5 hours
[0047] H2 and Ar2 mixed gas flow rate: 30ml / h
[0048] Water content dew point: -15℃
[0049] After cooling, the metal oxide film was formed on the surface of the furnace tube by scanning electron microscope and energy dispersive spectrometer analysis.
[0050] Table 1 Figure 1 .
[0051]
[0052] Table 1: Distribution of composition elements before and after surface treatment of furnace tube in Example 1
[0053] from Figure 1 As can be seen from Table 1, before treatment, there are more iron and nickel elements on the surface, which are potential alloy elements that cause furnace tube coking. After low oxygen partial pressure water oxidation treatment, its surface is mainly covered by Mn and Cr element metal oxide film, forming a dense metal oxide layer, and the iron and nickel content is significantly reduced. The iron and nickel elements are shielded, and coking is significantly reduced. Figure 1 It can be seen that the surface of the alloy is covered with MnCr2O4 spinel, and the inner surface shows the Al2O3 structure and (Cr, Al)2O3 corundum structure generated in the bottom layer from the peeling area. Figure 1 It can be seen that naphtha was used as the cracking raw material, and a coking test was carried out on the furnace tube of Example 1 after heat treatment under a low oxygen partial pressure water oxidation atmosphere.
[0054] The coking test conditions are as follows:
[0055] Raw materials: industrial naphtha;
[0056] Naphtha physical properties: distillation range 60-120;
[0057] Lysis time: 2 hours;
[0058] Cracking temperature: 850℃;
[0059] Preheating temperature: 750℃;
[0060] Preheating time: 20min;
[0061] After cooling, weigh and compare.
[0062] Example 2
[0063] In order to explore the effect of adding aluminum to form a composite oxide layer on the furnace tube alloy, Example 2 uses furnace tube alloys with different aluminum contents (Al content: 0, 6) to perform low oxygen partial pressure treatment in the same water oxidation test as Example 1, and a gas mixture of H2, Ar2 and H20 is used as a low oxygen partial pressure water oxidation atmosphere. In the low oxygen partial pressure water oxidation atmosphere gas of the gas mixture of H2, Ar2 and H20, the volume percentage of H20 in the low oxygen partial pressure water oxidation atmosphere gas is 0.132%.
[0064] The specific processing conditions are as follows:
[0065] Divided into low temperature treatment and high temperature treatment
[0066] Low temperature oxidation temperature: 750℃
[0067] Oxidation time 5 hours
[0068] H2 and Ar2 mixed gas flow rate: 30ml / h
[0069] Water content dew point: -15℃
[0070] High temperature treatment
[0071] High temperature treatment oxidation temperature: 1050℃
[0072] Oxidation time 5 hours
[0073] H2 and Ar2 mixed gas flow rate: 30ml / h
[0074] Water content dew point: -15℃
[0075] After cooling, the results were analyzed by scanning electron microscope and energy dispersive spectrometer. Figure 4 , Figure 5 , Table 2.
[0076] Spectrum O Al Si Cr Mn Fe Ni Y Nb 0Al 58.17 0 1.40 19.56 5.10 8.06 7.85 -0.20 0.06 6Al 46.78 15.39 1.79 7.22 0.04 13.07 14.55 0.24 0.92
[0077] Table 2 shows the element composition and element distribution of the furnace tube surface with different Al contents in Example 2 after water oxidation treatment
[0078] from Figure 4 , Figure 5It can be seen from Table 2 that when the Al content is 0%, the bottom aluminum oxide layer cannot be generated, the diffusion rate of alloy elements increases, and the surface layer is covered by MnCr2O4 spinel, which cannot provide a good shielding effect on iron and nickel elements. Increasing the Al content will enhance the external oxidation of Al and reduce the external oxidation rate of Cr and Mn alloys. In addition, due to the strict Al2O3 generation process, the surface aluminum oxide generation is low, the surface oxide density is reduced, the metal oxide film is thin, and the shielding of iron and nickel elements is reduced, resulting in an increase in the diffusion rate of Fe and Ni. The same coking test as in Example 1 is used:
[0079] The coking test conditions are as follows:
[0080] Raw materials: industrial naphtha;
[0081] Naphtha physical properties: distillation range 60-120;
[0082] Lysis time: 2 hours;
[0083] Cracking temperature: 850℃;
[0084] Preheating temperature: 750℃;
[0085] Preheating time: 20min;
[0086] After cooling, weigh and compare
[0087] Experimental results show that the coking weight gain of the furnace tube in Example 1 after heat treatment in a low oxygen partial pressure water oxidation atmosphere is 0.2585 mg / cm 2 , Example 2 is compared with Example 1, and the coking weight gain of 0% Al is 0.4329 mg / cm 2 , the coking weight gain of 6% Al is 0.8413 mg / cm 2 The preferred Al content is 4%.
[0088] Comparative Example 1
[0089] The preferred components are 35% Ni, 25% Cr, 4% Al, 1.5% Mn, 1.5% Nb, 1.5% Si, 1% W, 0.5% Zr, 0.4% C, 0.06% Y, and the balance is Fe in weight percentage, and are centrifugally cast into the required furnace tube. After processing, the surface is bright and free of oxide scale.
[0090] The furnace tube alloy was oxidized in an air oxygen test apparatus, using air as the treatment gas. The specific treatment conditions are as follows:
[0091] Oxidation temperature: 1000℃
[0092] Oxidation time: 10 hours
[0093] Oxidizing atmosphere: air
[0094] After cooling, the results were analyzed by scanning electron microscope and energy dispersive spectrometer. Figure 2 , Table 3.
[0095]
[0096] Table 3: Distribution of composition elements before and after surface treatment of furnace tube in Comparative Example 1;
[0097] from Figure 2 As can be seen from Table 3, after being treated with air, the iron and nickel content on the surface decreased slightly and was covered by a portion of oxides. However, the diffusion of iron and nickel elements could not be blocked, and the high iron and nickel content would cause coking. Figure 2 It can be seen that after long-term oxidation at high temperature, the surface Cr2O3 becomes loose and porous, and Fe and Ni phases are precipitated, which does not hinder Fe and Ni.
[0098] Using the same cracking raw materials and cracking test conditions as in Example 1, a coking test was carried out on the furnace tube treated with air atmosphere in Example 1.
[0099] The coking test conditions are as follows:
[0100] Raw materials: industrial naphtha;
[0101] Naphtha physical properties: distillation range 60-120;
[0102] Lysis time: 2 hours;
[0103] Cracking temperature: 850℃;
[0104] Preheating temperature: 750℃;
[0105] Preheating time: 20min;
[0106] Weigh and compare after cooling.
[0107] Experimental results show that the coking weight gain of the furnace tube in Example 1 after heat treatment in a low oxygen partial pressure water oxidation atmosphere is 0.2585 mg / cm 2 The coking amount of the furnace tube treated by oxidation in air in Comparative Example 1 is 1.8465 mg / cm 2 A reduction of 86%.
[0108] Comparative Example 2
[0109] The commonly used furnace tube HK40 alloy furnace tube is preferred, which has a bright surface and no oxide scale after processing.
[0110] The furnace tube alloy was used to perform low oxygen partial pressure treatment in a water oxidation test, using a gas mixture of H2, Ar2 and H20 as a low oxygen partial pressure water oxidation atmosphere. In the low oxygen partial pressure water oxidation atmosphere gas of the gas mixture of H2, Ar2 and H20, the volume percentage of H20 in the low oxygen partial pressure water oxidation atmosphere gas was 0.132%.
[0111] The specific processing conditions are as follows:
[0112] Divided into low temperature treatment and high temperature treatment
[0113] Low temperature oxidation temperature: 750℃
[0114] Oxidation time 5 hours
[0115] H2 and Ar2 mixed gas flow rate: 30ml / h
[0116] Water content dew point: -15℃
[0117] High temperature treatment
[0118] High temperature treatment oxidation temperature: 1050℃
[0119] Oxidation time 5 hours
[0120] H2 and Ar2 mixed gas flow rate: 30ml / h
[0121] Water content dew point: -15℃
[0122] After cooling, the results were analyzed by scanning electron microscope and energy dispersive spectrometer. Figure 3 , Table 4.
[0123]
[0124] Table 4: Distribution of composition elements before and after surface treatment of HK furnace tube in Comparative Example 2
[0125] from Figure 3 As can be seen from Table 4, after HK40 alloy is oxidized by water, the iron and nickel content on its surface decreases and is covered by a portion of oxides. The iron and nickel elements will still diffuse outward, causing coking. Figure 3 It can be seen that the surface is covered by Cr2O3 and (Fe, Cr)2O3 spinel, but the density is not enough and the barrier to Fe and Ni is limited.
[0126] After cooling, the same cracking raw materials and cracking test conditions as in Example 1 were used, and the coking test was carried out on the furnace tubes treated with water oxidation in the low oxygen pressure atmosphere in Comparative Example 2.
[0127] The coking test conditions are as follows:
[0128] Raw materials: industrial naphtha;
[0129] Naphtha physical properties: distillation range 60-120;
[0130] Lysis time: 2 hours;
[0131] Cracking temperature: 850℃;
[0132] Preheating temperature: 750℃;
[0133] Preheating time: 20min;
[0134] Weigh and compare after cooling.
[0135] Experiments have shown that the weight gain of the furnace tube in Example 1 after heat treatment in a low oxygen partial pressure water oxidation atmosphere is 0.2585 mg / cm 2 The coking amount of HK40 alloy after heat treatment in low oxygen partial pressure water oxidation atmosphere is 1.0189 mg / cm 2 A decrease of 74.63%.
[0136] The detailed description of the technical solution of the present invention in the above embodiments is illustrative rather than restrictive. Technicians engaged in related work can use the method of the present invention for detection, and all modifications and changes within the spirit and scope of the present invention are included in the protection scope of the present invention.
Claims
1. A coking and creep resistant cracking furnace tube, characterized in that: The surface layer of the furnace tube is a MnCr2O4 spinel oxide layer, and the inner surface gradually changes into an (Al, Cr)2O3 corundum oxide layer and an Al2O3 oxide layer; The chemical composition of the furnace tube includes, by mass percentage, 35% Ni, 25% Cr, 4% Al, 1.5% Mn, 1.5% Nb, 1.5% Si, 1% W, 0.5% Zr, 0.4% C, 0.06% Y, and the balance is Fe; The method for preparing the anti-coking and anti-creep cracking furnace tube is as follows: According to the chemical composition of the furnace tube, the furnace tube is manufactured by centrifugal casting, and then the furnace tube is heat-treated in a low oxygen partial pressure water oxidation atmosphere, wherein the low oxygen partial pressure water oxidation atmosphere is a gas mixture of H2, Ar and H2O; The heat treatment in a low oxygen partial pressure water oxidizing atmosphere is firstly low temperature heat treatment and then high temperature heat treatment; During low temperature heat treatment, the heat treatment temperature is 600-750°C, the heat treatment time is 5-10 hours, and the dew point of the low oxygen partial pressure water oxidation atmosphere is -10°C~-20°C; During high temperature heat treatment, the heat treatment temperature is above 1050°C, the heat treatment time is 3-10 hours, and the dew point of the low oxygen partial pressure water oxidation atmosphere is -15°C~-20°C; H2O is controlled by a micro pump to set a predetermined amount of water, and is vaporized in a preheating furnace. A mixed gas of H2 and Ar is introduced into the preheating furnace at a rate of 30 mL / h to mix with water vapor, and then enters the reaction furnace for oxidation reaction. In the low oxygen partial pressure water oxidation gas: the H2 content accounts for 4% of the volume of the low oxygen partial pressure water oxidation gas, the H2O content accounts for 0.001%~3% of the volume of the low oxygen partial pressure water oxidation gas, and the rest is Ar.
2. The anti-coking and anti-creep cracking furnace tube according to claim 1, characterized in that: In the method for preparing the anti-coking and anti-creep cracking furnace tube, the heat treatment in a low oxygen partial pressure water oxidizing atmosphere is firstly low temperature heat treatment and then high temperature heat treatment; During low temperature heat treatment, the heat treatment temperature is 600-750°C, the heat treatment time is 5-10 hours, and the dew point of the low oxygen partial pressure water oxidation atmosphere is -10°C~-20°C; During high temperature heat treatment, the heat treatment temperature is above 1050°C, the heat treatment time is 3-10 hours, and the dew point of the low oxygen partial pressure water oxidation atmosphere is -15°C~-20°C; H2O is controlled by a micro pump to set a predetermined amount of water, and is vaporized in a preheating furnace. A mixed gas of H2 and Ar is introduced into the preheating furnace at a rate of 30 mL / h to mix with water vapor, and then enters the reaction furnace for oxidation reaction. In the low oxygen partial pressure water oxidation gas: the H2 content accounts for 4% of the volume of the low oxygen partial pressure water oxidation gas, the H2O content accounts for 0.001%~3% of the volume of the low oxygen partial pressure water oxidation gas, and the rest is Ar.
Citation Information
Patent Citations
Cracking furnace tube for inhibiting catalytic coking of hydrocarbon cracking furnace tube, and manufacturing method thereof
CN102807887A